On the diurnal cycle of surface energy fluxes in the North American monsoon region using the WRF‐Hydro modeling system. Issue 17 (4th September 2017) - Xiang, Tiantian; Vivoni, Enrique R.; Gochis, David J.; Mascaro, Giuseppe
Abstract: The diurnal cycles of surface energy fluxes are important drivers of atmospheric boundary layer development and convective precipitation, particularly in regions with heterogeneous land surface conditions such as those under the influence of the North American monsoon (NAM). Characterization of diurnal surface fluxes and their controls has not been well constrained due to the paucity of observations in the NAM region. In this study, we evaluate the performance of the uncoupled WRF‐Hydro modeling system in its ability to represent soil moisture, turbulent heat fluxes, and surface temperature observations and compare these to operational analyses from other commonly used land surface models (LSMs). After a rigorous model evaluation, we quantify how the diurnal cycles of surface energy fluxes vary during the warm season for the major ecosystems in a regional basin. We find that the diurnal cycle of latent heat flux is more sensitive to ecosystem type than sensible heat flux due to the response of plant transpiration to variations in soil water content. Furthermore, the peak timing of precipitation affects the shape and magnitude of the diurnal cycle of plant transpiration in water‐stressed ecosystems, inducing mesoscale heterogeneity in land surface conditions between the major ecosystems within the basin. Comparisons to other LSMs indicate that ecosystem differences in the diurnal cycle of turbulent fluxes are underestimated in these products. While this study shows how land surface heterogeneity affects the simulated diurnal cycle of turbulent fluxes, additional coupled modeling efforts are needed to identify the potential impacts of these spatial differences on convective precipitation. Key Points: WRF‐Hydro reproduces observed soil moisture, turbulent fluxes, and land surface temperature at individual sites and as spatial patterns Diurnal cycle of latent heat flux varies among ecosystems due to plant transpiration and is affected by the peak timing of precipitation Stomatal control on plant transpiration induces mesoscale heterogeneity in the diurnal cycle of the turbulent fluxes within a regional basin